Cooperative effects of metal cations and coordination modes on luminescent s-block metal–organic complexes constructed from V-shaped 4, 4′-sulfonyldiphenol. Issue 46 (9th November 2018) - Li, Cheng; Deng, Zhao-Peng; Huo, Li-Hua; Gao, Shan
Abstract : Thirteen s-block metal–organic complexes with different supramolecular networks arising from the coordination modes of the ligands and properties of the metal cations have been synthesized and exhibit violet and blue luminescence in the solid state at room temperature. Abstract : The self-assembly of 4, 4′-sulfonyldiphenol (H2 sdp) with s-block metal salts in an aqueous or mixed H2 O/alcohol solution gives rise to the formation of 13 new complexes, namely, [Li(Hsdp)(H2 O)] n (1 ), [Na(Hsdp)(H2 O)] n (2 ), [K(Hsdp)(H2 sdp)(H2 O)] n (3 ), [Cs(Hsdp)(solvent)(H2 O)] n [solvent = EtOH (4 ) and i-PrOH (5 )], [Mg(H2 O)6 ]·2(Hsdp)·(H2 sdp)·4H2 O (6 ), [Ca(Hsdp)2 (H2 O)4 ] (7 ), [AE2 (Hsdp)4 (H2 sdp)4 ] [AE = Sr (8 ) and Ba (9 )], [Mg(sdp)(H2 O)] n (10 ), [Ca(sdp)] n (11 ), [Sr(sdp)(H2 O)2 ] n (12 ), and [Ba2 (sdp)2 (MeOH)2 (H2 O)] n (13 ), which have been characterized by elemental analysis, IR spectroscopy, TGA, PL, and powder and single-crystal X-ray diffraction. The smaller Li(i ) and Na(i ) cations in complexes1 and2 tend to induce the formation of chain and layer structures, whereas the larger K(i ) and Cs(i ) cations in complexes3, 4 and5 tend to induce the formation of a 3-D hybrid network. Complexes6–9 and10–13 also exhibit an increase in dimensionality in the sequence from Mg(ii ) to Ba(ii ) cations. From a reaction at room temperature, mononuclear (6 and7 ) and dinuclear (8 and9 ) motifs are observed. In contrast, from a hydrothermal reaction, layer (10 and12 ) and 3-D hybrid (11 and13 ) networks are formed with less coordination of water molecules and more intricate coordination modes of sdp 2− dianions. The structural evolution is mainly determined by the effective coordination numbers (ECNs) and radii of the metal cations, as well as the coordination modes of the ligands. As a result of hydrogen bonding, these 13 complexes possess various types of network, i.e., porous networks with rhombic or hexagonal channels, organic–inorganic hybrid networks, and ABAB packing networks. The solid-state luminescence properties demonstrate that all these complexes exhibit violet and blue emissions in the range of 375–429 nm at room temperature.